Growth Mindset sebagai Mediator antara Komunikasi Guru terhadap School Well-Being Siswa di Kota Bekasi - Afrina Sari (Jurnal Ilmiah Psikologi MIND SET, 2021)
School well-being is related to students' subjective assessment about their school. School well-being has four dimensions, having (school conditions), loving (school relationships), being (self-fulfillment), and health. School well-being will be felt better by students, if the teacher's communication is better done to students. And the growth mindset becomes a mediation for students that must be developed. This study aims to examine the mediator variable, growth mindset, which is a mediator between teacher communication affecting school well-being. The research method uses correlational quantitative methods. The population was 480 students, and sample was 214 students, which were taken based on Morgan's table. The results showed that there was a significant and positive effect at the level of p=0.05. Teacher's communication on school well-being with a growth mindset as a mediator shows the Sobel test score of 2.207, and can be interpreted that the growth mindset is feasible as a mediator.